Microsoft PowerPoint 2010 plain & simple - Muir, Nancy 1954- (O'Reilly Media, 2010)
"With this full color, no-nonsense guide, you'll learn the quickest ways to create a presentation with Microsoft PowerPoint 2010. Easy-to-follow steps and concise, straightforward language make learning plain and simple."
Print version record
Keywords: Microsoft PowerPoint (Computer file); Presentation graphics software; COMPUTERS; Desktop Applications; Presentation Software